OPTIMASI PERTUMBUHAN MICROGREEN RED RADISH MELALUI OTOMATISASI PENYIRAMAN, PENYINARAN, DAN PENYESUAIAN SUHU BERBASIS IOT - Safitrah, Tiara; Khabibah, Dea Ummul; Ezer, Angga Eben; Fernando, Brilliant Sandynigy; Kauripan, Edmund Banyu; Satrio, Muchammad Alifandino; Maulidan, Muhammad Hafizh; A'isy, Nabil Arif; Marcelita, Faldiena; Fathonah, Lathifunnisa (Universitas Semarang, 2024)
This research aims to optimize the growth of red radish microgreens through an automation system that integrates irri-gation, lighting, and temperature adjustment based on the Internet of Things (IoT). The research method involves the use of WS2812B LED strips as the lighting source for photosynthesis, soil moisture sensors to control irrigation, and DHT22 tem-perature sensors to adjust the ideal environmental temperature. Data collection combines relevant literature data with direct observations during the red radish microgreen planting process. Data analysis is conducted through descriptive approaches to understand the growth patterns of microgreen plants and correlation analysis to identify relationships be-tween various growth parameters. Additionally, the IoT system's response to changes in environmental conditions is ana-lyzed to evaluate the system's effectiveness in regulating lighting, irrigation, and temperature. The research findings indi-cate that the IoT-based automation system effectively enhances the growth and quality of red radish microgreens. The au-tomatic implementation of LEDs improves photosynthesis rates, while efficient irrigation systems ensure plants receive adequate water. The temperature automation system maintains optimal growth conditions and reduces the risk of thermal stress. Integrating this system into a website platform also enables remote control and monitoring. This automation system not only increases plant productivity and quality but also reduces maintenance costs and time, demonstrating the signifi-cant potential of IoT technology in modern agriculture. Keywords: Automation System, Growth, Internet of Things, Microgreen, Red Radish. ABSTRAK Penelitian ini bertujuan untuk mengoptimalkan pertumbuhan microgreen red radish melalui sistem otomatisasi yang mengintegrasikan penyiraman, penyinaran, dan penyesuaian suhu berbasis Internet of Things (IoT). Metode penelitian melibatkan penggunaan LED strip WS2812B sebagai sumber pencahayaan untuk fotosintesis, sensor kelembaban tanah untuk mengontrol penyiraman, dan sensor suhu DHT22 untuk menyesuaikan suhu lingkungan yang ideal. Pengumpulan data dalam penelitian menggabungkan data literatur yang relevan serta pengamatan langsung selama proses penanaman microgreen red radish. Analisis data dilakukan melalui pendekatan deskriptif untuk memahami pola pertumbuhan tana-man microgreen dan analisis korelasi untuk mengidentifikasi hubungan antara berbagai parameter pertumbuhan. Selain itu, respons sistem IoT terhadap perubahan kondisi lingkungan dianalisis untuk mengevaluasi efektivitas sistem dalam mengatur pencahayaan, penyiraman, dan suhu. Hasil penelitian menunjukkan bahwa sistem otomatisasi berbasis IoT efektif dalam meningkatkan pertumbuhan dan kualitas microgreen red radish. Penerapan LED secara otomatis meningkatkan laju fotosintesis, sementara sistem penyiraman efisien memastikan tanaman mendapatkan air yang tepat. Sistem otomatisasi suhu menjaga lingkungan pertumbuhan optimal dan mengurangi risiko stres termal. Integrasi sistem ini dalam platform website juga memungkinkan kontrol dan pemantauan secara remote. Sistem otomatisasi ini tidak hanya meningkatkan produktivitas dan kualitas tanaman, tetapi juga mengurangi biaya dan waktu pemeliharaan, menunjukkan potensi besar teknologi IoT dalam pertanian modern.